Lipid Profile and Blood Glucose Levels of Wistar Rats Fed a Non-High Fat Nutriment Supplemented with Black Garlic Extract - R. Susanti; K. Kristamtini (International Journal of Food Studies)
Many studies related to the therapeutic effect of black garlic (BG) have been carried out on cancer, diabetes, neurodegenerative, cardiovascular, dyslipidemia and other diseases. This investigation was conducted to examine the effect of BG supplements on the lipid profile and blood glucose of rats fed a customary diet (non-high fat diet). A fermented black garlic product was extracted by a maceration method and its phytochemical components were analyzed using LCMS. Black garlic extract was given to healthy rats with a normal feed for 14 days. Twenty-four rats were divided into 4 groups of 6 rats. As a control, group A was given aquadest (placebo), and groups B, C, and D were given BG extract at a dose of 15 mg/kg BW, 30 mg/kg BW, and 45 mg/kg BW, respectively. On day 15, blood was taken from the retro-orbital plexus of the rats to measure the total levels of cholesterol, High-Density Lipoprotein-Cholesterol (HDL-C), Triglyceride (TG), Low-Density Lipoprotein-Cholesterol (LDL-C) and glucose. Black garlic made by fermentation at 80°C for 8 days contained more monosaccharides, disaccharides and oligosaccharides than fresh garlic. Black garlic contained 32 types of organosulfur compounds, and the 5 most abundant compounds were allicin (5.813%), allin (4.993%), isoallin (3.77%), cycloalliin (3.163%) and (-) S-allyl-L-cysteine (2.022%). Black garlic extract administration was able to maintain blood glucose homeostasis in rats fed a normal diet (non-high fat diet). Levels of total cholesterol, triglyceride, and LDL-C were significantly decreased in groups administered black garlic compared to the control group, whilst the level of HDL-C increased significantly in groups administered black garlic compared to the control group.